2023
DOI: 10.3390/photonics11010020
|View full text |Cite
|
Sign up to set email alerts
|

Partially Coherent Off-Axis Double Vortex Beam and Its Properties in Oceanic Turbulence

Luli Chen,
Guiqiu Wang,
Yan Yin
et al.

Abstract: A partially coherent off-axis double vortex beam (PCOADVB) composed of two off-axis vortices is theoretically presented. The analytical equations of a PCOADVB in oceanic turbulence are presented, and the intensity profiles and the number of coherence vortices of the PCOADVBs are investigated based on the derived expressions. The numerical results show that the intensity profiles of PCOADVBs are determined by the initial topological charges M1 and M2 and the positions of the off-axis vortices (x1d,y1d) and (x2d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Underwater wireless optical communication (UWOC), which has the advantages of large bandwidth, high transmission rate and good confidentiality, has attracted the attention of a wide range of researchers [1,2]. Vortex beams, characterized by their possession of orbital angular momentum (OAM), with each photon carrying an OAM value of m 0 ÿ, where unlimited index m 0 represents the topological charge and ÿ is reduced Planck constant, can provide another degree of freedom for multiplexing applications due to the orthogonality among different OAM indexes [3][4][5][6][7][8]. It has been shown that the OAM multiplexing technique can significantly enhance the transmission efficiency of UWOC systems [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Underwater wireless optical communication (UWOC), which has the advantages of large bandwidth, high transmission rate and good confidentiality, has attracted the attention of a wide range of researchers [1,2]. Vortex beams, characterized by their possession of orbital angular momentum (OAM), with each photon carrying an OAM value of m 0 ÿ, where unlimited index m 0 represents the topological charge and ÿ is reduced Planck constant, can provide another degree of freedom for multiplexing applications due to the orthogonality among different OAM indexes [3][4][5][6][7][8]. It has been shown that the OAM multiplexing technique can significantly enhance the transmission efficiency of UWOC systems [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%